An inventory of measure for urban road sustainability - Sharinatol Akmanida Jamaludin,; Samikhah Muhammad,; Mohamad Razuhanafi Mat Yazid, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Sustainable transportation policies aim to reduce the negative impact on society, the environment, and the economy in urban areas. Sustainable transportation is an indicator to achieve the sustainability of urban areas. However, an inventory system to measure the level of sustainability of a road has not yet been established. Therefore, the Sustainable Transportation Inventory System (STIS) was developed as an initial assessment of road sustainability in urban areas using the software. Through a literature review, ten criteria from social, environmental, and economic indicators were identified. Findings of these criteria are compiled into an inventory system using Microsoft Excel software. STIS consists of five worksheets namely metric criteria, social, environmental, economic, and score calculation. This inventory calculates the score and level of road sustainability of urban areas based on the guidelines that have been identified. Results from expert evaluation through Ipoh City Council (MBI), Public Works Department (PWD) and Town and Country Planning Department (JPBD) in Perak showed STIS with ten criteria approved for testing in selected urban areas. STIS improvements can be structured for use in other cities in Malaysia concerning relevant guidelines and are easily accessible using smartphones.